Integrated H∞ filtering bumpless transfer control for switched linear systems. (November 2019) - Zhao, Ying; Zhao, Jun; Fu, Jun; Dimirovski, Georgi M.
Abstract: The integrated H ∞ filtering bumpless transfer control problem for switched linear systems is studied in this paper. The target is to attain the H ∞ filtering property of the switched linear systems via switchings, while reducing the control bumps induced by switchings. First, a novel description of the bumpless transfer performance is presented, quantifying the suppression level on the control bumps from both relative and absolute viewpoints. Then, a switching logic, a collection of filters and filter-based controllers are jointly designed to attain this target. Further, a criterion which ensures not only the H ∞ filtering property but also the bumpless transfer performance is developed. Finally, an application on a turbofan engine control system model is offered, verifying the efficiency of the developed integrated H ∞ filtering bumpless transfer control strategy. Highlights: Bumpless transfer control issue with H ∞ filtering property is firstly studied. A novel bumpless transfer performance concept is proposed from its original purpose. Establish a criterion to realize the bumpless transfer performance and the H ∞ filtering property. Apply the developed control strategy to a turbofan engine model.